Multilevel innovation platforms for development of smallholder livestock systems: How effective are they? - Lema, Zelalem; Bruyn, L.A.L. de; Marshall, G.R.; Roschinsky, R.; Duncan, Alan J. (Elsevier, 2021)
There is growing recognition that sustainable development of smallholder agriculture in Sub-Saharan Africa requires a systems approach. One response to this has been applying the agricultural innovation systems concept and the use of Innovation Platforms (IP) as tools for agricultural development. By providing social space and facilitating interactions among farmers, researchers and other stakeholders, IPs can promote collective action and foster innovation. The question is, how effective are these IPs in stimulating innovation that can be sustained beyond their lifetime, and can they be used to link issues across multiple scales? The case study reported here examined the effect of a multilevel IP structure in achieving smallholder livestock innovation outcomes in the Ethiopian Highlands. Two years after the multilevel IPs were phased out, focus group discussions and key informant interviews with multiple stakeholders from all levels of the IP were undertaken to collect qualitative data on the innovation processes and analysed using thematic analysis. Our findings indicate that a series of IPs inter-linked across scales facilitated researcher-led technical innovations that enhanced farmers and livestock experts' capacity around feed technologies. The multilevel IPs also improved linkages and strengthened partnerships between actors within and across levels to effectively implement farm-level technologies. However, sustained innovation requires creating a shared understanding among actors on the complex nature of the various value chain issues that need to be addressed to achieve meaningful change. Specifically, we found that farmers lack access to affordable services. This requires integrating value chain concepts within multilevel IPs at the early stages of formation to engage relevant actors across levels to stimulate multiple interventions beyond the farm-level. Changes are needed at the organisational level to facilitate reconfiguration of resources and devolution of responsibilities to support the innovation process. The existence of power dynamics and an institutional context favouring the status quo are key issues that need to be considered when building and evaluating effective multilevel IPs to achieve inclusive value chain innovations.